Edukasi Pentingnya Menjaga Kelestarian Lingkungan Berbasis Ekowisata di Pantai Cemara Desa Ciheras - Putri, Meirin Dwiningtyas; Nurazizah, Ayi; Mutiara, Risa; Nurlaela, Ela; Ristianisa, Rissa; Rismalasari, Risma; Titin, Titin (Yayasan Inspirasi El Burhani, 2025)
Introduction: Cemara Beach in Ciheras Village, Cipatujah District is one of the tourist attractions in Tasikmalaya Regency that has considerable potential to be used as ecotourism. However, these aquatic resources have not been utilized as ecotourism areas due to the lack of information about the potential known to the community Objective: The purpose of this service was to provide education about the importance of environmental sustainability and to recognize the potential of Cemara Beach which can be used as ecotourism. Method: This public service is carried out using the counseling or socialization method so that it is hoped that the community can understand the importance of preserving the environment of Cemara Beach and recognize the potential of Cemara Beach which can be used as an ecotourism development. Result: The results show that the community is able to understand the importance of preserving the environment and can recognize the potential of Cemara Beach which can be used as ecotourism by independently developing Cemara Beach ecotourism. Conclusion: Community service activities in Ciheras Village received a positive response from the community that the importance of educating people about preserving the environment based on ecotourism means utilizing the coastal environment without damaging or disturbing the environment and culture of the local community.